2002
DOI: 10.1042/bj20020491
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the nitration of γ-tocopherol in vivo: 5-nitro-γ-tocopherol is elevated in the plasma of subjects with coronary heart disease

Abstract: This study investigated the hypothesis that nitration of gamma-tocopherol may be an important mechanism for the detoxification of reactive nitrogen oxide species in vivo. Using liquid chromatography-tandem MS we have shown that gamma-tocopherol can be nitrated in vivo to form 5-nitro-gamma-tocopherol and that concentrations of this compound are elevated in the plasma of subjects with coronary heart disease. In addition, we demonstrate in carotid-artery atherosclerotic plaque that nitration of gamma-tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…Possible artefactual nitration of ␥T during analysis was excluded by appropriate in vitro experiments. Compared to the analysis of NGT using LC-MS (18) or CoulArray detection (29), the present method requires somewhat less expensive equipment and, at the same time, offers an at least 50-fold higher sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible artefactual nitration of ␥T during analysis was excluded by appropriate in vitro experiments. Compared to the analysis of NGT using LC-MS (18) or CoulArray detection (29), the present method requires somewhat less expensive equipment and, at the same time, offers an at least 50-fold higher sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a CoulArray system is considerably more expensive. More recently, an LC-MS/MS method was described and used for the measurement of NGT in plasma of normal human subjects and subjects with coronary heart disease (18). The advantage of this method is that NGT is unambiguously analyzed by specific detection of the nitrated chomanol ring fragment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14) 5-Nitro--tocopherol has been detected in human plasma and in plant tissues, and is considered to be a biomarker for oxidative stress. 15,16,26) -Tocopherol has also reacted with hypochlorous acid, a potential biological oxidant and electrophile, to form 5-chloro--tocopherol and other chlorinated products.…”
Section: Discussionmentioning
confidence: 99%
“…14) It has been demonstrated that -tocopherol was a target for nitration in vivo since the concentration of 5-nitro--tocopherol was elevated in the plasma of subjects with coronary heart disease 15) and in the plasma of smokers. 16) Supplementation with -tocopherol resulted in a significant reduction of urinary nitrotyrosine, a biomarker of nitrosative stress, in subjects with metabolic syndrome.…”
mentioning
confidence: 99%